Patterns of head shape and scutellation in Drymarchon couperi (Squamata: Colubridae) reveal a single species - Guyer, Craig; Folt, Brian; Hoffman, Michelle; Stevenson, Dirk; Goetz, Scott M.; Miller, Melissa A.; Godwin, James C. (Zootaxa, 2019)
Krysko et al. (2016a) used analyses of DNA sequence data to reveal two genetic lineages of Drymarchon couperi. The Atlantic lineage contained specimens from southeastern Georgia and eastern peninsular Florida, and the Gulf Coast lineage contained specimens from western and southern peninsular Florida as well as western Florida, southern Alabama, and southern Mississippi. In a second paper Krysko et al. (2016b) analyzed morphological variation of the two lineages, which allowed them to restrict D. couperi to the Atlantic lineage and to describe the Gulf Coast lineage as a new species, Drymarchon kolpobasileus. This taxonomic discovery was remarkable for such a large, wide-ranging species and was notable for its impact on conservation. Because of population declines, particularly in western Florida, southern Alabama, and southern Mississippi, D. couperi (sensu lato) was listed as Threatened under the Endangered Species Act (United States Fish and Wildlife Service 1978, 2008) and repatriation of the species to areas where it had been extirpated was listed as a priority conservation goal (United States Fish and Wildlife Service 1982, 2008). Such repatriation efforts were attempted in Alabama, Florida, Georgia, and South Carolina, starting in 1977 (Speake et al. 1987), but failed to create viable populations, likely because too few snakes were released at too many sites (Guyer et al. 2019; Folt et al. 2019a). A second attempt at repatriation was started in 2010 and concentrated on release of snakes at a single site in Alabama (Stiles et al. 2013). However, Krysko et al. (2016a) criticized this repatriation effort because it appeared to involve release of D. couperi (sensu stricto) into the geographic region occupied by D. kolpobasileus (as diagnosed in Krysko et al. 2016b).